2017
DOI: 10.3390/tropicalmed2020018
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Strongyloides stercoralis Faecal Larvae Detections in the Northern Territory, Australia: 2002 to 2012

Abstract: Strongyloides stercoralis is a soil-transmitted helminth (STH) endemic to tropical and subtropical areas. We reviewed the temporal detection trends in patients with S. stercoralis larvae present in faecal samples, in Northern Territory (NT) Government Health facilities, between 2002 and 2012. This was a retrospective observational study of consecutive patients with microbiologically confirmed detection of S. stercoralis in faeces. The presence of anaemia, eosinophilia, polyparasitism, and geographic and demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…Children are over-represented in population estimates of strongyloidiasis. A Territory-wide study examining faecal larval detection between 2002 and 2012 found that children under five represented 42.2% of diagnoses, with rates of 3–6% of stool samples examined compared to 1.7% of samples overall [ 9 ]. A study of patients diagnosed with strongyloidiasis by faecal microscopy at Royal Darwin Hospital also identified that patients under five years of age were disproportionately represented, with 54% of cases falling in this age group [ 13 ].…”
Section: Review Of Endemic Strongyloidiasis Epidemiology In Austramentioning
confidence: 99%
See 2 more Smart Citations
“…Children are over-represented in population estimates of strongyloidiasis. A Territory-wide study examining faecal larval detection between 2002 and 2012 found that children under five represented 42.2% of diagnoses, with rates of 3–6% of stool samples examined compared to 1.7% of samples overall [ 9 ]. A study of patients diagnosed with strongyloidiasis by faecal microscopy at Royal Darwin Hospital also identified that patients under five years of age were disproportionately represented, with 54% of cases falling in this age group [ 13 ].…”
Section: Review Of Endemic Strongyloidiasis Epidemiology In Austramentioning
confidence: 99%
“…The Strongyloides genus includes over fifty species capable of establishing parasitic infections in a range of animal hosts, and two species are known to infect humans [ 8 ]. Strongyloides fuelleborni is present in Papua New Guinea and Africa, while S. stercoralis is endemic throughout southern Europe, Africa, Asia, the Americas, and the northern two-thirds of Australia [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They each contribute to a much better understanding of Neglected and Emerging Tropical Diseases in South and Southeast Asia and Northern Australia. The contributions to these topics can be summarized as follows: four submissions on LFs [ 2 , 3 , 4 , 5 ], four submissions on STHs [ 6 , 7 , 8 , 9 ], two submissions on rickettsial diseases [ 10 , 11 ], and one submission on arboviral diseases [ 12 ]. A systematic review and meta-analysis leads the opening section on LF [ 2 ], which reviews prevalence and disease burden of LF in southeast Asia [ 2 ].…”
mentioning
confidence: 99%
“…A review paper leads the other major section on STH, which focuses on the prevalence of STHs in different groups, including immigrants, travellers, military personnel and veterans in Australia and Asia [ 6 ]. This is followed by studies examining an extended period of surveillance data on Strongyloides stercoralis [ 7 ]; and a study examining the prevalence of STHs in remote Aboriginal communities, both in the Northern Territory, Australia [ 8 ]; and a study examining the links between dietary intake, nutritional status, and intestinal parasites, such as Schistosoma japonicum , Ascaris lumbricoides , Trichuris trichiura , and hookworm, in the Philippines [ 9 ]. The two rickettsial papers examine hospital admissions for Queensland tick typhus in north Brisbane, Australia [ 10 ], and the other study based in Thailand looks at the influence of land use on scrub typhus in rodents [ 11 ].…”
mentioning
confidence: 99%